(untitled) (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: The paper’s primary goal is to report the devastating impact of carbon tetrachloride (CCl4) on rat testicular tissue and the possible protecting function of propolis against CCl4 based on its free radical scavenging and inflammatory relief properties. Materials and Methods: A total of 24 adult male albino rats had been classified into four groups (six rats/group). Rats of group 1 served as control, whereas groups 2–4 received propolis (200 mg/kg/day), CCl4 (3 ml/kg/day), and propolis/CCl4, respectively. After 4 weeks, the collected sera were applied for the estimation of lipid profile and sex hormones. Also, histopathological picture, malondialdehyde, and tumor necrosis factor alpha (TNFα) gene profile was measured in collected testicular tissues. Results: The present information revealed a noteworthy change (p < 0.05) in lipid profile, decrease in testicular weight, testosterone, antioxidants values along with a prominent increase (p < 0.05) in estradiol, lipid peroxidation values, and expression of TNFα in rats administrated with CCl4 compared to control. Moreover, the histopathological profile showed the degeneration of the epithelium. Interestingly, propolis attenuated the destructive effect of CCl4 on rat testes. Conclusion: The examined dose of propolis reduced oxidation, and inflammatory reactions resulted from CCl4 exposure and proved that it might have a helpful part in free radicals interceded diseases. J. Adv. Vet. Anim. Res., 8(1): 70-77, Mar 2021 http://doi.org/10.5455/javar.2021.h487